Design, Cultivation and Application of Load-Bearing Mycelium Components: The MycoTree at the 2017 Seoul Biennale of Architecture and Urbanism. Issue 1 (June 2018) - Heisel, Felix; Lee, Juney; Schlesier, Karsten; Rippmann, Matthias; Saeidi, Nazanin; Javadian, Alireza; Nugroho, Adi Reza; Mele, Tom Van; Block, Philippe; Hebel, Dirk E.
No abstract available